Determination of Six Macrolide Antibiotics in Chicken Sample by Liquid Chromatography-Tandem Mass Spectrometry Based on Solid Phase Extraction. (24th February 2019) - Lan, Chen; Yin, Dan; Yang, Zhicong; Zhao, Wuduo; Chen, Yanlong; Zhang, Wenfen; Zhang, Shusheng
Abstract : In this paper, a simple and effective method for the determination of six macrolide antibiotics (MACs), including tylosin, tilmicosin, azithromycin, clarithromycin, roxithromycin, and kitasamycin, in the chicken sample using liquid chromatography-tandem mass spectrometry (LC-MS/MS) was developed based on a self-built porous aromatic framework- (PAF-) based solid phase sorbent. The main parameters influencing the extraction efficiency, such as sorbent amounts, type of the eluent, pH of the sample, and the eluent volume, were evaluated. Under the optimized condition, the limits of detection were from 0.2 to 0.5 μ g·kg −1 . The recoveries of the method ranged from 82.1% to 101.4% with the relative standard deviations less than 11.1%. All the results demonstrated that the established method is potential for the determination of macrolide antibiotics in food safety analysis and monitoring.